Analysis of Water Evaporation and Drift Losses during Irrigation in Semi-arid Areas of Sharjah (UAE) and Riyadh (KSA) - Al Naizy, Raafat (2012)
Water evaporation and wind drift losses mainly depend on air relative humidity, air and water temperature, drop size, and wind speed. Evaporation and drift loss during water application by means of sprinkle irrigation was studied in the Emirate of Sharjah, United Arab Emirates (UAE) and Riyadh, Saudi Arabia. Results for both cities did not vary substantially due to high relative humidity even under high air temperature. Results indicated that evaporation losses are usually <5% under any climatological conditions in the two Gulf cities. For night time watering to be considered, extra-costs (e.g., electricity, manpower) should not exceed potential savings.